Expert-level classification of gastritis by endoscopy using deep learning: a multicenter diagnostic trial - Mu, Ganggang; Zhu, Yijie; Niu, Zhanyue; Li, Hongyan; Wu, Lianlian; Wang, Jing; Luo, Renquan; Hu, Xiao; Li, Yanxia; Zhang, Jixiang; Hu, Shan; Li, Chao; Ding, Shigang; Yu, Honggang (Endoscopy International Open, 2021)
Background and study aims Endoscopy plays a crucial role in diagnosis of gastritis. Endoscopists have low accuracy in diagnosing atrophic gastritis with white-light endoscopy (WLE). High-risk factors (such as atrophic gastritis [AG]) for carcinogenesis demand early detection. Deep learning (DL)-based gastritis classification with WLE rarely has been reported. We built a system for improving the accuracy of diagnosis of AG with WLE to assist with this common gastritis diagnosis and help lessen endoscopist fatigue.Methods We collected a total of 8141 endoscopic images of common gastritis, other gastritis, and non-gastritis in 4587 cases and built a DL -based system constructed with UNet + + and Resnet-50. A system was developed to sort common gastritis images layer by layer: The first layer included non-gastritis/common gastritis/other gastritis, the second layer contained AG/non-atrophic gastritis, and the third layer included atrophy/intestinal metaplasia and erosion/hemorrhage. The convolutional neural networks were tested with three separate test sets.Results Rates of accuracy for classifying non-atrophic gastritis/AG, atrophy/intestinal metaplasia, and erosion/hemorrhage were 88.78 %, 87.40 %, and 93.67 % in internal test set, 91.23 %, 85.81 %, and 92.70 % in the external test set ,and 95.00 %, 92.86 %, and 94.74 % in the video set, respectively. The hit ratio with the segmentation model was 99.29 %. The accuracy for detection of non-gastritis/common gastritis/other gastritis was 93.6 %.Conclusions The system had decent specificity and accuracy in classification of gastritis lesions.DL has great potential in WLE gastritis classification for assisting with achieving accurate diagnoses after endoscopic procedures.